Semicircle : A Case Study on Concept of Trigonometrical Ratios of Acute Angles - Manoj Kumar Srivastav (International Journal of Mathematics And its Applications, 2015)
Trigonometric ratios of an acute angle in a right angle triangle express the relationship between the angle and length of its sides. Angles in a semicircle is a right angle. The angle inscribed in a semicircle is always 90^° In the present paper, author tried to present the properties of semicircle in which it is possible to explain the concept regarding trigonometric ratios of acute angles.